2008
DOI: 10.1016/j.ijpharm.2007.10.050
|View full text |Cite
|
Sign up to set email alerts
|

Key functions in polymer carriers for intestinal absorption of insulin

Abstract: This work aimed to clarify the relationship between polymer function and insulin absorption, and to evaluate the optimized preparative formulation predicted from this relationship.Insulin-loaded polymer (ILP) carrier systems were prepared following a two-factor composite second-order spherical experimental design. To investigate the polymer function, we evaluated its insulin release, bioadhesiveness, and protective effect. Each ILP was administered intestinally, and glucose reduction was monitored as the pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Nakamura et al recently reported their findings on insulin absorption as a function of polymer properties, and developed a system, namely multivarient spline interpolation [31]. They reported that with the help of this mathematical approach, an optimized formulation was predicted, as well as how polymer function affects insulin absorption.…”
Section: Nanoparticles: a Probable Solution For Oral Insulin Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Nakamura et al recently reported their findings on insulin absorption as a function of polymer properties, and developed a system, namely multivarient spline interpolation [31]. They reported that with the help of this mathematical approach, an optimized formulation was predicted, as well as how polymer function affects insulin absorption.…”
Section: Nanoparticles: a Probable Solution For Oral Insulin Deliverymentioning
confidence: 99%
“…Nakamura et al reported that the enzymatic degradation of insulin was reduced in a concentration-dependent manner with respect to the amount of polymer added [31]. They observed at least a 50% reduction in insulin degradation even with low amounts of poly methacrylic acid-g-poly ethylene glycol, which is attributed to the inhibitory effect exerted by the anionic polymer.…”
Section: Enzyme Inhibitorsmentioning
confidence: 99%
“…In addition, insulin denaturation has been indicated as one of the causes of failure in the preparation of insulin delivery systems [14]. Therefore, albumin coating has been indicated to avoid degradation of insulin by proteases, preventing they can reach the insulin inside the nanoparticles, giving stability to the system in the stomach [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the present study was to assess the feasibility of formulating lipospheres of Pioglitazone HCl by melt dispersion technique and obtaining a suitable release pattern. [1][2][3][4][5] cetyl alcohol, gelatin were purchased from S.D. Fine Chemicals Ltd. (India).…”
Section: Introductionmentioning
confidence: 99%